Inventory Of Predatory Insects In Banana Germplasm Umbulharjo Yogyakarta - Putra, Ichsan; Sahnan, Hastin Nur Samsia (Journal of Biotechnology and Natural Science, 2021)
One  of  the  beneficial  insects  in  agriculture  and  plantations  is a predator. Using natural predators  to  control pests and diseases certainly has advantages. The purpose of this study was to calculate the level of predatory insect diversity in banana germplasm plantations and find the most abundant and least abundant predatory insects. The independent variable in this study is the banana germplasm plantation area, and the dependent variable in this study is the diversity and dominance of predatory insects found in the research location. Sampling in this study using a random method. The sweep net was in the morning, while the pitfall was collected, installed in the morning and taken in the afternoon. Predatory insect data analysis used in this study is to use the scan now-wiener diversity index and the Simpson dormancy index. The results showed that the predatory insects that mainly were found were the species, Paratrechina longicornis while the least that was found was the species Ischiodon scutellaris. From other results, namely the level of predatory insect diversity obtained, the results show that Yogyakarta banan germ plantation have moderate diversity of predatory insects. The conclusion of this study is that there is a disturbance in the Giwangan Banana Germplasm Garden Yogyakarta due to insects, so that the diversity index is moderate, while the predominance of predatory insects is 0.484, which means that in the ecosystem, one predatory insect is found that dominates.